Diagnostic utility of neutrophil lymphocyte ratio in acute complicated cholecystitis (Annals of Medical Research, 2021)
None
Keywords: s: Acute Cholecystitis; C-Reactive Protein; Neutrophil-To-Lymphocyte Ratio.